Standardization one methodology for to germinate seeds of interspecific hybrid Elaeis oleifera H.B.K. X Elaeis guineens - Guerrero, Jennifer; Bastidas, Silvio; García, Javier (Revista de Ciencias Agrícolas, 2011)
In the Experimental Station El Mira of Corpoica, located in the municipality of Tumaco, Colombia, it carried out this investigation justified by the low percentage of germination of seeds of the hybrids Elaeis oleifera x Elaeis guineensis. For this, it was evaluated the effect of three treatments: Stratum (External, Middle, Internal); Humidity of the seeds (18%-22%, 20%-24%, 22%-26%) and Days of heating (60, 70,80,90 and 100 days at39°C) using an experimental design in Randomized Blocks with 3x3x5+3 in factorial arrangement, with 3 replications of 50 seeds each (45 OxG treatments and 3 Tènera treatments control). The methodology used was based on the protocol for germination of Tènera seeds of the species Elaeis guineensis. The ANOVA indicated significant differences for Stratum, Humidity of the seeds, Days of heating and for the interaction Humidity of the seeds*Days of heating. It was found that: seeds of the External stratum of the bunch, germinates 8.9% and 14.3% more than the Middle and Internal stratum, respectively. The best treatment for germinating OxG seeds was the following combination of pre-treatments: Soaking until the seeds reach 20% humidity, then to apply heat for 70 days at 39°C and finally put to germinate when the seeds reached 24% moisture in the second period of soaking, with this treatment was achieved an average of 40.37% germination. It identified that in addition to low germination, the hybrids have low vigor germination, defined as the time elapsed from the time the first seeds germinate until the end of the period of germination, due to differential maturation of the embryos.